EFFECT OF CONCENTRATION AND FREQUENCY CROCOBER PLUS AS ORGANIC LIQUID FERTILIZER GIVING ON THE ONION CROPS (Allium ascalonicum L.) - Munir, Jamilah Munir; Novita, Elvera Novita (LLDIKTI Wilayah X, 2014)
Research on the effect of liquid organic fertilizer (POC) Crocober plus and frequency of application to the crop of onion (Allium ascalonicum L.) had been conducted in Sub Kajai, District lemur, Solok regency for 3 months starting from May to July 2015. The goal was to get the POC concentration and Crocober plus frequency to increase growth and yield of onion. Experiments using a randomized block design in a factorial form that consists of 2 factors. Factor 1 was 5 degree of concentration POC was 0% (P0), 2.5% (P1), 5% (P3), 7.5% (P4) and 10% (P5) while Factor 2, was the frequency of POC consists of two levels ie ; The data obtained and analyzed variance. If the F count larger than F table 5% followed by a test of Duncan Multiple Range Test (DMRT). The experimental results indicated that application of 5% POC Crocober plus concentration given weekly was the exact interaction to improve the growth and yield of onion with the result reached 13.83 tons/ha.Doi: 10.22216/jit.2014.v8i2.340